URINE KETONE LEVELS IN TUBERCULOSIS PATIENTS IN THE TELAGA DEWA COMMUNITY HEALTH CENTER AREA OF BENGKULU CITY IN 2025 - Putri Rahmadani; Putri Widelia Welkriana; Wiwit Sulistyasmi (Poltekkes Kemenkes Banten, 2026)
Ketonuria, the presence of ketones in urine, occurs when the body breaks down fat as energy due to a lack of carbohydrates. This process produces ketone bodies (acetone, acetoacetic acid, 3-hydroxybutyric acid). This condition often occurs in people with tuberculosis (TB) due to decreased appetite and side effects of medications that cause a lack of carbohydrate intake. Tuberculosis is a global infectious disease, where Indonesia has the second highest cases in the world. In Bengkulu City, tuberculosis cases are increasing, with the Telaga Dewa Health Center recording the most cases. Tuberculosis is caused by the bacterium Mycobacterium tuberculosis which is airborne and is risky for all ages. This study aims to find out the description of urine ketone in tuberculosis patients at the Telaga Dewa Health Center, Bengkulu City in 2025. The sample in this study was 27 people using the accidental sampling method. The examination was carried out using the rothera method. The results of the distribution of urine ketone frequency in tuberculosis patients were obtained with 15% positive urine ketone and 85% negative urine ketone results. Based on the results of the research on Urinary Ketone, overview in Tuberculosis Patients at the Telaga Dewa Health Center, Bengkulu City in 2025 on 27 samples, the following results were obtained 15% were positive for urinary ketone. The results of this study are expected for the community, especially tuberculosis patients, to maintain good health and diet.